RELASI KUASA DALAM PERUBAHAN SENI TARI GANDRUNG DI DESA KEMIREN, KECAMATAN GLAGAH, KABUPATEN BANYUWANGI - Pakarti, Dian; Kebayantini, Ni Luh Nyoman; Krisna Aditya, I.G.N Agung (JURNAL ILMIAH SOSIOLOGI (SOROT), 2020)
ABSTRACT This research focuses on change of Gandrung dance. The background of this research is the view of Islamic religious leaders who view the Gandrung dance as an art that is not in accordance with religious principles. The theory used is Michel Foucault's Power of Relation theory. The results showed that the Gandrung dance had changed due to the power of knowledge that was continuously produced by Islamic religious figures on Gandrung dance then causing this dance to undergo changes in various aspects: changes in dancers from male to female, song changes, changes in the paju stage and the last change in Gandrung dance is change of clothes. The positive impact of this art becomes more politely and closed in terms of appearance while the negative impact is the loss of philosophical values ??and local wisdom contained in the dance of Gandrung dance. Keywords: power relations, change, gandrung dance